Obstacles, Networking Approaches and Entrepreneurial Network Changes. Issue 2 (22nd May 2018) - Soetanto, Danny; Huang, Qihai; Jack, Sarah
Abstract : While recent work has considered network change, little is known about how certain factors determine such changes. This study focuses on two factors – the type of obstacles entrepreneurs face and their networking approach – and employs a two‐stage research design and network visualisation approach to capture entrepreneurs' experiences in managing networks during their entrepreneurial journey. Using an inductive approach, the first stage of the study identifies the obstacles and networking approaches that influence different types of network changes. The second stage employs a deductive approach to test the hypotheses developed from the first stage using a larger sample. We find that in experiencing obstacles from internal sources, entrepreneurs are more likely to find support from weak ties while strong ties are beneficial for overcoming obstacles from external sources. In having difficulties in acquiring entrepreneurial knowledge and skills, entrepreneurs are more likely to develop a low‐density network consisting of many structural holes. Conversely, dealing with difficulties in accessing market and resources imposes over‐reliance on high‐density network. Furthermore, the entrepreneurs' networking approaches also influence network changes and partially mediate the relationship between the networks and the obstacles they face.